A Model for Enhancing Organizational Capacity in State Islamic Higher Education Institution Study Programs to Achieve International Reputation - Zuhriyah, Indah Aminatuz; Padil, Moh; Hidayat, Hidayat; Hidayati, Suci; Wahidmurni, Wahidmurni (AL-ISHLAH: Jurnal Pendidikan, 2024)
Capacity building in organizations is an innovative strategy aimed at enhancing efficiency, effectiveness, productivity, and accountability to achieve global recognition. This article investigates organizational capacity building within the Doctoral Study Program in Islamic Education Management at the Postgraduate Program of the State Islamic University of Maulana Malik Ibrahim Malang, an institution committed to attaining an international reputation. Using a qualitative approach and descriptive analysis, data were gathered through interviews, observation, and documentation. The study reveals that: (1) the development of organizational capacity to achieve international recognition focuses primarily on human resource development and organizational strengthening; (2) visionary leadership is the most crucial factor in reaching international status; and (3) the process of building organizational capacity involves socializing the goals of international recognition, empowering existing resources, managing the transition through the ADKAR Prosci model, and striving to become an internationally recognized Islamic university. These findings suggest that enhancing organizational capacity in an effective, efficient, and sustainable manner can significantly improve the productivity, performance, and accountability of study programs, contributing to their international reputation.